Book review: Narasimhan Srinivasan and Girija Srinivasan, State of India's Livelihood Report 2017. (August 2019) - Bhattacharya, Niloshree
Narasimhan Srinivasan and Girija Srinivasan, State of India's Livelihood Report 2017 . New Delhi: SAGE Publications, 2018, 198 pp., ₹1945 (Paperback). ISBN: 978-93-528-0580-8.